Les Représentations de Soi et de L’autre a Travers L’utilisation de la Concession Argumentative - Boumaza, Karima; Boudechiche, Nawal (جامعة عنابة, 2020)
انطلاقا مما جاء به كل من بيرلمان وتيتيكا من مفاهيم، سنحاول من خلال هذه الدراسة البحث عن الوسائل التي تساعد الطلبة المسجلين بقسم اللغة الفرنسية (ليسانس وماستر) في إتقان التعبير الجدلي. وعلى هذا الأساس، نفترض أن التنازل كأسلوب بلاغي وحركة جدلية يرتكز في الأساس، كما هو معروف، على تسوية تنشأ بين صورة المجادل وصورة الجمهور الذي يحاول إقناعه، أي بث روح الأخلاق والشفقة بين الطرفين المتقابلين. وبهذا نكون قد ساهمنا في تحديد صورة المجادل والآخر من خلال الحركة الجدلية. Drawing on Perelman & Obrechts- Tyteca’s work, we are questioning as a corollary the means that would enable students enrolled in a bachelor's and master's degree in French as a foreign language to succeed in their argumentative writing. Thus, we postulate that the concession, as a rhetorical figure and argumentative movement, is notoriously based on a compromise established between the image of the argumentator and that of the public he aims to convince; the ethos and pathos of the two antagonistic parts. Our contribution thus identifies the image of the argumentator and the other through this argumentative movement.
Keywords: التنازلات الجدلية -- اللغة الفرنسية -- الحركة الجدلية